Implementasi Kalman Filter Pada Kendali Roket EDF - Wisnu Pamungkas; Bakhtiar Alldino Ardi Sumbodo; Catur Atmaji (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2017)
EDF (electric ducted fan) rocket is a flying object shapes like bullet with electric ducted fan motor as the booster. This rocket fly autonomously by utilizing accelerometer, gyroscop, and magnetometer sensor to determine the attitude of the rocket against the earth’s gravitational and magnetic field of the earth. In controlling the rocket required a control system capable of controlling a rocket with sensor data that has been processed into the value of the attitude that has been filtered.In this study, designed a filter that will be implemented on the microcontroller rocket. The filters are Kalman filter is implemented while the control used is the control proportional integral derivative (PID) with Ziegler-Nichols tuning method.The result of this research is an implementation of kalman filter to EDF rocket control system. Based on the experiment that has been done, control system using a Kalman filter has a standard deviation value against the value of linear regression on a roll attitude of 2.73, a pitch of 3.03, and yaw of 6.96 degrees. While the standard deviation of the ideal value on a roll attitude of 3.43, a pitch of 2.92 and yaw of 5.21 degrees.